Modulation of the orodigestive tract microbiome in HIV‐infected patients. (April 2016) - Saxena, D; Li, Y; Devota, A; Pushalkar, S; Abrams, W; Barber, C; Corby, P; Poles, M; Phelan, J; Malamud, D
Abstract : More than 37 million people are living with human immunodeficiency virus 1 (HIV), and more people than ever received lifesaving antiretroviral therapy worldwide. HIV‐1 infection disrupts the intestinal immune system, leading to microbial translocation and systemic immune activation. We investigated the impact of HIV‐1 infection on the GI microbiome and its association with host immune activation. The data indicated that the microbiome was different in HIV‐positive and HIV‐negative individuals. The initial sequence analysis of saliva indicated that there were major differences in the phyla of Bacteroidetes, Firmicutes, Proteobacteria, and TM7. Phylum Tenericutes was only seen in HIV‐positive saliva. At the family level, we identified differences in Streptococcacea, Prevotellaceae, Porphyromonadaceae, and Neisseriaceae, whereas data from various sites in GI tract indicated that Prevotella melaninigencia, Fusobacterium necrophorum, Burkholderia, Bradyrhizobium, Ralstonia, and Eubacterium biforme were predominant but differentially present at various sites. Furthermore, there was a decrease in seven proteins associated with the alternative complement pathway and an increase in 6 proteins associated with the lectin and classical complement pathways. The correlation with a shift in complement pathways suggests that compromised immunity could be responsible for the observed dysbiosis in the GI microbiome.